2020
DOI: 10.1111/1745-5871.12451
|View full text |Cite
|
Sign up to set email alerts
|

Untangling insurance, rebuilding, and wellbeing in bushfire recovery

Abstract: Home and contents insurance is framed as key to Australia's national strategy for disaster resilience. Despite the perceived importance of financial indemnity, ambiguity characterises the ways in which it facilitates both short‐ and long‐term everyday household recovery when disaster strikes. Addressing such ambiguity, this article explores how insurance impacts upon households' capacities to rebuild and recover after disastrous bushfire. In‐depth interviews conducted with residents in the Blue Mountains of Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…There is also a gap between the "logics" employed by insurers to assess claims and the logics through which policyholders assign value to their belongings (Booth & Harwood, 2016), rendering true "like for like" replacement of lost property impossible (McFall, 2011). Building on research on disaster recovery (Eriksen & de Vet, 2021;Gearing, 2018;He et al, 2021), our participants' experiences show that extended and onerous claims processes fail to deliver on policyholders' expectations of protection and peace of mind and exacerbate the trauma arising from disasters. For some survivors, being subject to a "prolonged" and "adversarial" claims process can be "the most distressing element of their recovery," on par with the disaster event itself (He et al, 2021, p. 10).…”
Section: Discussionmentioning
confidence: 96%
“…There is also a gap between the "logics" employed by insurers to assess claims and the logics through which policyholders assign value to their belongings (Booth & Harwood, 2016), rendering true "like for like" replacement of lost property impossible (McFall, 2011). Building on research on disaster recovery (Eriksen & de Vet, 2021;Gearing, 2018;He et al, 2021), our participants' experiences show that extended and onerous claims processes fail to deliver on policyholders' expectations of protection and peace of mind and exacerbate the trauma arising from disasters. For some survivors, being subject to a "prolonged" and "adversarial" claims process can be "the most distressing element of their recovery," on par with the disaster event itself (He et al, 2021, p. 10).…”
Section: Discussionmentioning
confidence: 96%
“…Parents' obligations and capacities to provide a sense of normalcy were compromised by longer term stability objectives. Rebuilding required seemingly endless interdependent processes and decisions at a time of "bushfire brain" (Eriksen & de Vet, 2020). Managing competing requirements became one of parents' "biggest" struggles, handled "day by day" (Heather), "one foot in front of the other" (Robert).…”
Section: Parenting After Bushfirementioning
confidence: 99%
“…While insurance systems are imperfect, they are pivotal to the National Strategy for Disaster Resilience (Council of Australian Governments (COAG), 2011;de Vet et al, 2019). After the 2013 Blue Mountains bushfires in New South Wales, insurance was found to alleviate household stress by providing certainty in house replacement and repair (de Vet & Eriksen, 2020). Yet, narrative interviews revealed that personal and situational factors provide a clearer determinant of the length and depth of recovery than insurance did (Eriksen & de Vet, 2020).…”
mentioning
confidence: 99%
See 2 more Smart Citations